2022
DOI: 10.52812/ijgs.62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chinese Cloth Suppliers using Dynamic Grey Relational Analysis

Abstract: The clothing industry is one of the world's most important and innovative industries. Furthermore, it is a major industry in developing economies such as China and India. With the global economic turmoil and environmental problems expanding, it is extremely important to choose suppliers who offer the highest level of customer satisfaction while taking environmental concerns into account. The study aims to evaluate wholesale clothing suppliers of a Chinese import/export company using the Dynamic Grey Relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In 2022, Javed et al (2022) overcame these shortcomings by proposing the Dynamic GRA model. Later, Ouali (2022) confirmed the model's validity while studying the supplier selection problem, whereas Mahmoudi and Javed (2023) used it to validate another MCDM model. The key components of the model are discussed below.…”
Section: Dynamic Grey Relational Analysismentioning
confidence: 94%
“…In 2022, Javed et al (2022) overcame these shortcomings by proposing the Dynamic GRA model. Later, Ouali (2022) confirmed the model's validity while studying the supplier selection problem, whereas Mahmoudi and Javed (2023) used it to validate another MCDM model. The key components of the model are discussed below.…”
Section: Dynamic Grey Relational Analysismentioning
confidence: 94%
“…Today, it has seen widespread applications in various fields. Among its core parts include the theories of Grey Numbers (Shajedul, 2021; Candra, 2022), Grey Decision-Making (Javed et al ., 2022; Mahmoudi et al ., 2021), Grey Linear Programming (Mahmoudi et al ., 2018), Grey Relational Analysis (Oyedeji et al , 2022; Abifarin and Ofodu, 2022; Ouali, 2022) and Grey Forecasting (Wu et al ., 2022; Tian et al ., 2021). Grey forecasting models are data-driven intelligent time-series forecasting systems that can predict future patterns of a variable with minimal data (Javed and Cudjoe, 2022; Zineb et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, Javed et al (2022) proposed an improved version of Deng's GRA model called the DGRA that overwhelmed the issue in the original model. Later studies have confirmed the validity of the improved model (Ouali, 2022;Ervural, 2023;Matambo, 2023). The steps involved in the execution of the DGRA model are given below: STEP 1.…”
Section: Dynamic Grey Relational Analysis Modelmentioning
confidence: 99%